Legal Policy in Preventing Economic Exploitation of Women through Online Loans Based on Gender Justice - Neri Tarigan, Luri (Jurnal Multidisiplin Sahombu, 2025)
The rapid growth of online loans in recent years has offered quick and accessible financial solutions to the public, including women. However, this convenience comes with significant risks, particularly economic exploitation of women who often face barriers in accessing financial information and education. This study aims to analyze existing legal policies in preventing such exploitation through a gender justice approach. The objective is to identify gaps in current regulations, including limited access to information, inadequate legal protection, and the lack of gender-sensitive principles in policymaking. Using a qualitative approach, this research explores the socio-economic vulnerabilities of women in the online lending context and emphasizes the need for improved regulatory frameworks. The findings reveal that current legal instruments fall short in addressing gender-based disparities and fail to provide adequate safeguards for women borrowers. The study recommends policy enhancements focusing on strengthening financial literacy, improving oversight of online lending practices, and embedding gender justice principles into the regulatory structure. Additionally, it highlights the crucial roles of government, financial institutions, and community organizations in building a protective and empowering ecosystem for women. The conclusion underscores the importance of policies that are responsive to women's socio-economic conditions and promote equitable financial access. By advancing inclusive and gender-responsive legal reforms, the study aims to foster a safer and more just financial system that protects and empowers women in the digital lending landscape.